Experimental and Theoretical Characterization, In Silico and In Vitro Studies of (E)-1-(5-Nitrothiophen-2-yl)-N-(2-(Trifluoromethyl)Phenyl)Methanimine - Seyhan Öztürk (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The current research was conducted to assess the in silico and in vitro potential of the heterocyclic Schiff base compound (E)-1-(5-nitrothiophen-2-yl)-N-(2-(trifluoromethyl)phenyl)methanimine(N2TPM). This Schiff base was synthesized according to the reported method using ethanol as solvent, and the reaction was monitored on TLC till completion of the reaction. The compound structure was elucidated using spectroscopic techniques such as UV/Vis, FT-IR, 1H-NMR, and 13C-NMR. Molecular structure was determined using a single XRD, which revealed that the compound was triclinic. Analysis of intermolecular interactions in crystalline compounds was performed using Hirshfeld surface analysis and 2D fingerprint plots. The structure of the compound was optimized using the B3LYP hybrid functional with the basis set 6-31G(d,p). The compound’s theoretical and experimental parameters (bond length, bond angle, molecular orbital energies, electronic transitions, and vibration frequencies) were compared with each other which are in close agreement. R² values were found to be 0.9914 for bond lengths and 0.9859 for bond angles. In vitro, esterase potential of the synthesized compound was checked using a spectrophotometric model, while in silico molecular docking studies were performed with Auto-dock against two enzymes of the esterase family. The docking studies and in vitro assessment predicted that such molecules could be used as enzyme inhibitors against tested enzymes; acetylcholine esterase (AChE) and butyrylcholine esterase (BChE). the compound showed a binding score of -10.4159, a binding energy of -10.2743 with AChE, a binding score of -10.3378 and a binding energy of -9.8889 with BChE.